Interpersonal Communication Through The Internet - Celalettin Aktaş (Selçuk İletişim)
The Internet has become a social environment where a large number of people all over world are connected to each other regardless of differing locations and timetables. Thus, this technology provides a place where people can meet to do business, to collaborate on a task, to solve problems, to organize a project, and to engage in personal conversation.  The development of computers and telecommunication technologies has also influenced the social life of individuals.  Through the Internet people can engage in personal conversation and create close relationships.  Such relationships even can end in marriage.  Especially match making and chat sites provided by the Internet transform interpersonal relationships into a new social place.  Therefore, this article focuses on how the internet technologies have changed relationships in the society and considers the characteristics of the resulting relationships, in comparison with face-to-face relationships.